2002
DOI: 10.1161/hc0902.104710
|View full text |Cite
|
Sign up to set email alerts
|

Endogenous Ligand of α 1 Sodium Pump, Marinobufagenin, Is a Novel Mediator of Sodium Chloride–Dependent Hypertension

Abstract: Background-Digitalis-like sodium pump ligands (SPLs) effect natriuresis via inhibition of renal tubular Na ϩ ,K ϩ -ATPase but may induce vasoconstriction. The present study investigated the potential roles of 2 putative endogenous SPLs, an ouabain-like compound (OLC) and an ␣ 1 Na ϩ ,K ϩ -ATPase inhibitor, marinobufagenin (MBG), in regulating natriuresis and blood pressure (BP) responses to sustained and acute NaCl loading in Dahl salt-sensitive rats (DS). Methods and Results-During 4 weeks of an 8% NaCl diet,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

20
190
2
4

Year Published

2005
2005
2021
2021

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 152 publications
(216 citation statements)
references
References 26 publications
20
190
2
4
Order By: Relevance
“…Because there is sufficient evidence that ouabain and marinobufagenin are likely the endogenous cardiotonic steroids, our findings brings about an interesting question as to whether this mode of regulation is relevant to in vivo physiology. To this end, several laboratories have reported that endogenous ouabain and marinobufagenin are circulated at sub-nM to nM concentrations in normal individuals and that volume expansion can significantly increase their concentrations (Hamlyn et al, 1991;Fedorova et al, 2002;Bauer et al, 2005). Thus, it is conceivable that the described regulation may be relevant to in vivo physiopathology if future in vivo studies confirm our in vitro experiments.…”
Section: Regulation Of Plc-␥1 and Ip3r2 By The Activated Na/katpase Ssupporting
confidence: 55%
“…Because there is sufficient evidence that ouabain and marinobufagenin are likely the endogenous cardiotonic steroids, our findings brings about an interesting question as to whether this mode of regulation is relevant to in vivo physiology. To this end, several laboratories have reported that endogenous ouabain and marinobufagenin are circulated at sub-nM to nM concentrations in normal individuals and that volume expansion can significantly increase their concentrations (Hamlyn et al, 1991;Fedorova et al, 2002;Bauer et al, 2005). Thus, it is conceivable that the described regulation may be relevant to in vivo physiopathology if future in vivo studies confirm our in vitro experiments.…”
Section: Regulation Of Plc-␥1 and Ip3r2 By The Activated Na/katpase Ssupporting
confidence: 55%
“…After acute and chronic salt-loading in these animals, a transient increase in circulating endogenous ouabain precedes a sustained increase in circulating marinobufagenin. 82,83 This observation has led us to postulate that endogenous ouabain, acting as a neurohormone, triggers release of marinobufagenin, which in turn causes increases in cardiac contractility, peripheral vasoconstriction and natriuresis by inhibiting the Na + /K + -ATPase (Figure 3). 102,103 We have subsequently demonstrated that the greatest transient increases in brain endogenous ouabain level occur in the amygdala, hippocampus and supraoptic nucleus of the hypothalamus.…”
Section: Interaction Between Endogenous Ouabain and Marinobufageninmentioning
confidence: 99%
“…The placentas were removed and placental and fetal weights determined. Blood was collected for Na,K-ATPase measurements in erythrocytes [14], and for plasma MBG measurements [13].…”
Section: Experimental Protocolmentioning
confidence: 99%
“…Activity of NKA in erythrocytes was determined, as reported previously in detail [14]. Erythrocytes were preincubated with Tween-20 (0.5%) in sucrose (250 mmol/L) and Tris buffer (20 mmol/L; pH 7.4, 37°C) for 30 minutes, and were incubated for 30 minutes in the medium (mmol/L): Na 100, K 10, MgCl 2 3, EDTA 0.5, Tris 50, ATP 2 (pH 7.4, 37°C) in the final dilution 1:40.…”
Section: Na/k-atpasementioning
confidence: 99%
See 1 more Smart Citation